IMPLEMENTASI PROGRAM JAMINAN KESEHATAN MASYARAKAT DIRUMAH SAKIT UMUM DAERAH Dr. SOETOMO SURABAYA (Studi Iniplementasi Program Jamkesmas Pada Aspek Pelayanan Bagi Pasien Luar Provinsi Di Rumah Sakit Umum Daerah Dr. Soetomo Surabaya) - Eny Maryati; Agus Subianto; Ismail (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2013)
RSUD Dr. Soetomo was the biggest hospital at East Indonesia that selected become one of recommended hospital to Jamkesmas patient from around of East Indonesia. That reason tfiat make searcher will concern searching to implementation Jamksesmas program that have been in Dr. Soetomo Hospital Surabaya especially to one of provinces patient. Problem resume in that searching was how did factors support and blocked implementation Jamkesmas program in Dr. Soetomo hospital The goal of this research is to descript about implementation of Jamkesmas program and factors that support and blocked to service aspect by patients from other. Method that have been used in this research was qualitative searching metode in the descript if type. Collecting file was did with indeepth interview technique, observation and documentation. Definite informan technique used key informan, that he or she know much about the field of this research titan other people around. File analyst process was did collecting also combain file that be goten and set up relation file network Searching product show that Jamkesmas program implementation and Dr. Soetomo hospital was transmission and consistency in communication, staff quality and quality progress method in staff sources, responding Jamkesmas subject and commitment disposition subject, level coordination and service standard in bureaucracy. Structure and factor blocked Jamkesmas program implementation was clear communication, staff quantity in the sources of staff and facility.